Analisis Kepuasan Penumpang Terhadap Kualitas Pelayanan Petugas Transit dan Transfer Di Bandar Udara Internasional Yogyakarta - Salsabilla Nova Regita Cahyani (Jurnal of Management and Social Sciences, 2024)
To achieve excellent service, a company’s employees must possess certain qualities, such as a passion for work and an attitude of always being ready to assist as well as having the capacity to handle customer complaints professionally. Service to service users at Yogyakarta International Airport, both at the departure terminal and arrival terminals, is critical for passengers. One of these is transit and transfer services for passengers. The purpose of this research is to find out the impact of Transit and Transfer officers’ service quality on passenger satisfaction and to identify what service quality attributes transit and transfer officers at Yogyakarta International Airport should develop. This research employed the importance-performance analysis (IPA) approach. The sample size was 100 respondents, obtained by distributing questionnaires to 100 respondents who were in transit or transferring at Yogyakarta International Airport and measured using the Slovin formula. The data were analyzed using Gap analysis with the SERVQUAL method and importance-performance analysis (IPA). The research results show that the analysis of the level of conformance and the reality-expectation gap based on the five SERVQUAL dimensions of the service quality of Transit and Transfer officers at Yogyakarta International Airport is good in satisfying passenger expectations. The average gap dimension analysis indicates that the service of Transit and Transfer officers are providing satisfactory service based on passengers’ perceptions, with an average score of <-1. Based on the Cartesian diagram mapping, 6 attributes are considered important by passengers and need priority action and carry out evaluations and improvements based on the mapping results through importance-performance analysis, with the physical evidence dimension resulting in the lowest quality dimension and requiring priority improvement action.